Bifurcation phenomena in a semiconductor superlattice subject to a tilted magnetic field - Anton O. Sel'skii; Alexander E. Hramov; Alexey A. Koronovskii; Olga I. Moskalenko; Alexander Balanov (2015)
The paper studies instabilities of charge transport in strongly coupled semiconductor superlattices with an applied electric and a tilted magnetic field. We reveal the bifurcation phenomena, which are associated with the transitions between different regimes of charge dynamics, and also investigate effects of the temperature on these bifurcations. In addition, we find out that the development of an instability can be accompanied by a graduate change of the dominant transport mechanism.